2014
DOI: 10.1586/14737140.2014.978293
|View full text |Cite
|
Sign up to set email alerts
|

Nanotube x-ray for cancer therapy: a compact microbeam radiation therapy system for brain tumor treatment

Abstract: Microbeam radiation therapy (MRT) is a promising preclinical modality for cancer treatment, with remarkable preferential tumoricidal effects, that is, tumor eradication without damaging normal tissue functions. Significant lifespan extension has been demonstrated in brain tumor-bearing small animals treated with MRT. So far, MRT experiments can only be performed in a few synchrotron facilities around the world. Limited access to MRT facilities prevents this enormously promising radiotherapy technology from rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…We found that microbeam radiotherapy using our desktop device and the irradiation protocol we utilized in the current study induced less neurocognitive impairment than the same integrated uniform dose on the hippocampal area in normal mice up to 8-month post-irradiation. Our previous studies demonstrated that applying MRT using our device is able to control the murine model of glioblastoma effectively [ 12 ]. This suggests that another potential advantage of MRT in brain tumor treatment is improved local tumor control rates with the ability to apply radiobiological higher doses either by re-irradiating of the same lesion using the same method or combining other radiation modalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that microbeam radiotherapy using our desktop device and the irradiation protocol we utilized in the current study induced less neurocognitive impairment than the same integrated uniform dose on the hippocampal area in normal mice up to 8-month post-irradiation. Our previous studies demonstrated that applying MRT using our device is able to control the murine model of glioblastoma effectively [ 12 ]. This suggests that another potential advantage of MRT in brain tumor treatment is improved local tumor control rates with the ability to apply radiobiological higher doses either by re-irradiating of the same lesion using the same method or combining other radiation modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, more recently, many groups, including Smyth et al [ 11 ], have emphasized the importance of evaluating chronic irradiation-induced changes by MRT treatment on a confined area of the brain. In the previous studies, we found that applying image-guided MRT using our novel method was able to induce tumor control in intracranial murine tumor model, without causing any significant histological changes up to 30 days post-irradiation [ 12 , 13 ]. However, our histology evaluations indicated that BB might cause more normal brain tissue damage than MRT in later time-points [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…This evolution has been previously reported for other biomaterial‐based scaffolds as well and indicates the strong material–cell interaction. The single cell alignment on the CNT substrates can be promising for performing single cell irradiation treatment experiments for pancreatic cancer . Formation of dense BxPC‐3 and PANC‐1 clusters is more characteristic on the CNT matrix as compared to the control substrate (in which there are many areas of single cell growth), while AsPC‐1 cells tend to form less dense clusters on both the control and the CNT sheers [Figure (a–f)].…”
Section: Resultsmentioning
confidence: 99%
“…2) versus 10 Gy with broad beam and found similar survival when employing 72-Gy irradiation or 10 Gy broad beam irradiation [37]. A review of the group's MRT work with CNTs can be found in [38].…”
Section: Microbeam Radiation Therapy (Mrt)mentioning
confidence: 99%